Hubungan Dukungan Keluarga dengan Kepatuhan Minum obat Pada Pasien Tuberculosis di Wilayah Kerja Puskesmas Plumbon Indramayu: Ike Widiyanti, Rudiansyah Rudiansyah - Widiyanti, Ike; Rudiansyah, Rudiansyah (Jurnal Persada Husada Indonesia, 2025)
Patient adherence to anti-tuberculosis (OAT) medication is a critical factor in the success of tuberculosis (TB) treatment. Various elements may influence this adherence, one of which is family support. This study aimed to examine the relationship between the level of family support and patient adherence to OAT consumption in the working area of the Plumbon Public Health Center. A quantitative method with a retrospective approach was employed. The sample consisted of 24 TB patients (total population). Data were collected using a questionnaire that had been tested for validity and reliability. The hypothesis test using the chi-square method revealed a significant relationship between family support and medication adherence among TB patients (p-value < 0.05). These findings indicate that family support plays an essential role in enhancing patients’ compliance with TB treatment. Therefore, family-based interventions may serve as an effective strategy to support the success of tuberculosis control programs.